Out of the Fringes. (Loppem : 't Wit Huis, 1990)
Amel, Gustaaf ; Amel, Valère ; Debolster, Mia ; Dejonckheere, Rudy ; Bogaerts, Karel ; Valentijns, Leon ; De Kock, Peter ; Van Coppenolle, Paul
Out of the Fringes, 't Wit Huis, Loppem, 9th - 27th July 1990
boek